A critical appraisal of fracture mechanics methods for self-healing and healable composites characterization. (April 2023) - Benazzo, F.; Rigamonti, D.; Sala, G.; Grande, A.M.
Abstract: Self-healing and healable Fibre Reinforced Polymer composites (FRPs) have tremendous potential in reducing the weight and increasing the lifetime of aerospace structures. While several strategies have been developed to add healing functionality to composites, there is no generally accepted method for the evaluation of their healing efficiency. Most testing approaches are based on interlaminar fracture toughness evaluation which revolves around three widely recognised methods: double-cantilever beam (DCB), three-point end-notch flexure (3-ENF), and four-point end notch flexure (4-ENF) testing. Alternative tests also employed in literature are low-impact velocity, micro-cutting, and short-beam shear (SBS) testing. This paper introduces the advantages and disadvantages of each test method when applied to healing FRPs while highlighting and explaining the large inconsistencies found among investigations. Ultimately, this review provides the necessary tools in choosing the most adequate test method for the characterization of a novel mendable FRP.